Exposing biology teachers' tacit views about the knowledge that is required for teaching using the repertory grid technique. (December 2015) - Rozenszajn, Ronit; Yarden, Anat
Highlights: Expert teachers hold tacit views about their teaching. Tacit views about teaching knowledge were exposed using the repertory grid technique. Content knowledge is an important knowledge component for biology teachers' practice. Biology teachers distinguish content knowledge from pedagogical content knowledge. Exposing biology teachers' tacit views may help to enrich their professionalism. Abstract: Several types of knowledge are known to be required for teaching, including content knowledge (CK) and pedagogical content knowledge (PCK). Exploring the relationships between CK and PCK is not a straightforward task due to their complex and tacit nature. Here we aim to expose biology teachers' views about the knowledge required for teaching biology and their tacit views about the relationships between CK and PCK using the repertory grid technique. Data collected from 23 in-service experienced high-school biology teachers revealed that CK is viewed by the participating teachers as an important component of knowledge for teaching. Analysis of their tacit views about the relationships between CK and PCK revealed that CK is viewed by and large as distinct from PCK.